Influence of lubrication, tool steel composition, and topography on the high temperature tribological behaviour of aluminium - Justine Decrozant-Triquenaux; Leonardo Pelcastre; Braham Prakash; Jens Hardell (Friction)
Abstract The use of high strength aluminium alloys, such as 6XXX and 7XXX series, is continuously increasing for automotive applications in view of their good strength-to-weight ratio. Their formability at room temperature is limited and they are thus often formed at high temperatures to enable production of complex geometries. Critical challenges during hot forming of aluminium are the occurrence of severe adhesion and material transfer onto the forming tools. This negatively affects the tool life and the quality of the produced parts. In general, the main mechanisms involved in the occurrence of material transfer of aluminium alloys at high temperature are still not clearly understood. Therefore, this study is focussed on understanding of the friction and wear behaviour during interaction of Al6016 alloy and three different tool steels in as-received and polished state. The tribotests were carried out under dry and lubricated conditions, with two distinct lubricants, using a reciprocating friction and wear tester. The worn surfaces were analysed using scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). The results showed a high dependence of friction and wear behaviour on the tool steel roughness as well as on the stability of the lubricant films. Tribolayers were found to develop in the contact zone and their capacity to improve the tribological behaviour is seen to be drastically impacted by the surface roughness of the tool steel. When the tribolayers failed, severe adhesion took place and led to high and unstable friction as well as material transfer to the tool steel.